SOCIAL PEDAGOGICAL EDUCATION IN WORK EDUCATION THE IMPORTANCE OF DEVELOPMENT (Archive of Conferences, 2021)
The article discusses the views on the development of social pedagogical thinking of youth and ensuring the effectiveness of teaching social sciences.